Ammonia Dispersion from Landfills (Case Study: Ganet Landfill, Tanjung Pinang) - Simbolon, Veronika Amelia; Pitriyanti, Luh; Daswito, Rinaldi; Martias, Indra (Public Health of Indonesia, 2025)
Background: Landfills are recognized sources of emissions of various gaseous pollutants, including ammonia (NH3), which can cause odor nuisances. The Ganet Landfill in Tanjungpinang City is currently managed using an open dumping system due to operational limitations. Objective: This study aimed to analyze the dispersion profile of ammonia gas originating from the Ganet Landfill and to examine the differences in its dispersion patterns between the rainy and dry seasons.Methods: Ammonia concentration data were collected based on one-hour average measurements at ten monitoring locations: one at the landfill unloading area and nine at surrounding points, including residential zones and adjacent roadways. These data were utilized as input for dispersion modeling using AERMOD software. Meteorological data for the year 2023 were estimated using historical data from 2019 to 2023 to support the modeling process.Results: The monitoring results indicated that ammonia concentrations at all measured locations complied with the quality standard of <2 ppm. AERMOD modeling for one-hour average concentrations showed that the highest predicted concentration within the landfill area was 0.08 μg/Nm3. In both the rainy and dry seasons, the dispersion of ammonia was predominantly toward the southwest, aligning with the prevailing wind direction in the area. The seasonal comparison revealed a difference in ammonia concentrations at a 7 km radius from the landfill center: 0.001 μg/Nm3 during the rainy season and 0.002 μg/Nm3 during the dry season.Conclusion: The modeling results corroborated the monitoring findings, indicating that the highest concentrations of ammonia occur at locations closest to the landfill, particularly in the southwest direction, consistent with the dominant wind patterns. Keywords: Ammonia; air pollution; dispersion modeling; landfill; seasonal variation